DAMPAK PANDEMI COVID-19 TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri Malfrita; Anjelita Sari (Jurnal Penelitian Ekonomi Akuntansi, 2022)
The purpose of this study was to determine changes in stock prices before and after the announcement of the entry of the Corona Virus (Covid-19) in Indonesia. The research was conducted on manufacturing companies and their sub-sectors on companies listed on the Indonesia Stock Exchange. This study uses a descriptive method with a quantitative approach, and uses secondary data in the form of closing stock price data obtained from the www.idx.co.id page. The data was taken only 5 months before and after the announcement of the entry of Covid-19 into Indonesia. The results of the study prove that the average share price of manufacturing companies on the Indonesia Stock Exchange experienced a sharp decline after the Covid-19 pandemic in Indonesia. However, there are several sub-sectors that only experienced a very small decline, namely the consumer goods sub-sector, the other miscellaneous industry sub-sector and the basic & chemical industry sub-sector (plastic and packaging).